Structuring And Fostering Traditional Markets, Shopping Centers, And Modern Stores At The Community Income Level - Siti Fatimah; Nadia Nisa Aulia; Miftahul Jannah; Siti Khumayah; Aghnia Dian Lestari (Journal Of Social Science (JoSS), 2024)
The market is a medium for bartering between the needs of sellers and buyers where sellers expect profits while buyers expect efficiency at very affordable prices. The purpose of this study is to explore the changes in the arrangement and guidance as well as the impact on the income level of the community after the fire. This research used a qualitative method with a case study approach. Three data collection techniques were used including observation, interview, and documentation. The research findings show that the authorized parties in implementing the policy are only the Cirebon Regency Trade and Industry Office. In terms of structuring, it is divided based on 3 elements, namely dry, semi, and wet zones. Based on Public Policy, structuring, and coaching have been implemented in accordance with government policy and in accordance with existing data. Policy Stakeholders have been well implemented, but not optimal because the traders are still not orderly and consumer interest is more to the marketplace making it easier for them to shop and more efficient in terms of time and expenses. Policy Environment has been well implemented, because it makes it easier for traders and consumers when selling and shopping. The conclusion of the impact on the income of business actors decreased due to a lot of competitiveness.